Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7732/kjpr.2014.27.6.714
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Protection and Anti-inflammatory Activity of Different Solvent Fractions from Aruncus dioicus var. kamtschaticus

Abstract: -This study investigated DNA damage protection and anti-inflammatory activity of different solvent fractions from Aruncus dioicus var. kamtschaticus (A. dioicus) aerial parts water extract. As for DNA damage protection, distilled water (H2O) fraction displayed the most powerful protection for DNA damage at a concentration of 1 ㎎/㎖. As for anti-inflammatory activity, dichloromethane (CH2Cl2) fraction exhibited the highest NO inhibition activity, ranging from 61% to 19% (10-40 ㎍/㎖). Furthermore, the levels of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…A. dioicus var. kamtschaticus has been known to be effective for anti‐inflammation (Zhang & Kim, ) and ischemic‐induced cell death (Lim & Lee, ). Previous studies showed that the ethyl acetate fraction from A. dioicus var.…”
Section: Introductionmentioning
confidence: 99%
“…A. dioicus var. kamtschaticus has been known to be effective for anti‐inflammation (Zhang & Kim, ) and ischemic‐induced cell death (Lim & Lee, ). Previous studies showed that the ethyl acetate fraction from A. dioicus var.…”
Section: Introductionmentioning
confidence: 99%
“… 2011 ; Youn et al. 2012 ; Zhang Q and Kim 2014 ). It shows a wide range of morphological variations, resulting in taxonomic confusion (Hara 1957 ; Cuizhi and Alexander 2003 ).…”
mentioning
confidence: 99%
“…H. Hara 1955 is a common East Asian variety, found in mixed forests at high elevation (Ohwi 1965;Cuizhi and Alexander 2003). In Korea, it has been traditionally used for foods (Chung et al 2010) and for medicinal and cosmetic usages (Kim M-S et al 2011;Youn et al 2012;Zhang Q and Kim 2014). It shows a wide range of morphological variations, resulting in taxonomic confusion (Hara 1957;Cuizhi and Alexander 2003).…”
mentioning
confidence: 99%
“…Through various studies, various physiological activities of Aruncus dioicus var. kamtschaticus in have been proved [11,12,13,14]. In animal experiments, it has been confirmed that the Aruncus dioicus var.…”
Section: Discussionmentioning
confidence: 96%
“…In in vitro study, it is reported that the extract of Aruncus dioicus var. kamtschaticus protects DNA damage and inhibits the NO activity as well as levels of pro-inflammatory cytokines mRNA expressions in lipopolysaccharide (LPS) stimulated RAW 264.7 cells [12]. It is confirmed that Aruncus dioicus var.…”
Section: Introductionmentioning
confidence: 92%